Securing hospital data: Blockchain-enhanced electronic health record solutions - Abu Hurerah; Hafiz Tamoor Shehzad; Muhammad Adnan Anwar; Mudassar Razzaq; Marcus Becker (Books on Demand (BoD), 2025)
Managing electronic health records (EHRs) within hospitals presents significant challenges, particularly in ensuring the security, privacy, and accessibility of sensitive patient data. Traditional systems are often vulnerable to breaches and inefficiencies, demanding the need for exploration of innovative technologies. This paper proposes a blockchain-based electronic health records (BbEHR) system utilizing the Ethereum blockchain and Flutter framework to create a decentralized, immutable, and tamperproof platform for hospital management. The Ethereum blockchain's smart contract functionality provides secure storage and guarantees data integrity, while the Flutter framework enables the development of responsive and visually appealing user interfaces across multiple devices. This decentralized approach enhances data privacy, accessibility, and system resilience against failures, offering a transformative solution for EHR management. The proposed system has the potential to secure healthcare data management by providing a secure, efficient, and user-friendly platform that meets the stringent requirements of modern healthcare institutions, adding the fact that introducing a BbEHR would minimize the danger of manipulating patient data due to its decentralized structure including unique cryptography methods for reaching consensus in each block of the chain.
Keywords: 650